The RNA helicase Dbp10 coordinates assembly factor association with PTC maturation during ribosome biogenesis - Mitterer, Valentin; Hamze, Hussein; Kunowska, Natalia; Stelzl, Ulrich; Henras, Anthony K.; Hurt, Ed (Nucleic acids research, 2024)
During ribosome biogenesis a plethora of assembly factors and essential enzymes drive the unidirectional maturation of nascent pre-ribosomal subunits. The DEAD-box RNA helicase Dbp10 is suggested to restructure pre-ribosomal rRNA of the evolving peptidyl-transferase center (PTC) on nucleolar ribosomal 60S assembly intermediates. Here, we show that point mutations within conserved catalytic helicase-core motifs of Dbp10 yield a dominant-lethal growth phenotype. Such dbp10 mutants, which stably associate with pre-60S intermediates, impair pre-60S biogenesis at a nucleolar stage prior to the release of assembly factor Rrp14 and stable integration of late nucleolar factors such as Noc3. Furthermore, the binding of the GTPase Nug1 to particles isolated directly via mutant Dbp10 bait proteins is specifically inhibited. The N-terminal domain of Nug1 interacts with Dbp10 and the methyltransferase Spb1, whose pre-60S incorporation is also reduced in absence of functional Dbp10 resulting in decreased methylation of 25S rRNA nucleotide G2922. Our data suggest that Dbp10's helicase activity generates the necessary framework for assembly factor docking thereby permitting PTC rRNA methylation and the progression of pre-60S maturation. Graphical Abstract
Gesehen am 22.04.2024
Online veröffentlicht: 19 Dezember 2023